PENGARUH CASH HOLDING, PROFITABILITAS DAN REPUTASI AUDITOR PADA PERATAAN LABA - Surya Dewi, Ni Made Sintya; Latrini, Made Yenni (E-Jurnal Akuntansi; Vol 15 No 3 (2016), 2016)
Income smoothing is one of the pattern of earnings management conducted by managers to reduce fluctuations in reported earnings that looks stable earnings from period to period thereafter. So that investors do not misjudging a company, investors need to consider factors that affect income smoothing so that investors can avoid the opportunistic behavior of managers. The purpose of this was to obtain empirical evidence about the effect of cash holding, profitability and reputation of auditors on income smoothing. Samples in this research are all companies listed on the Stock Exchange in 2010 – 2013 totaling 161 companies and 644 observations. Sampling technique using purposivesampling. The analysis technique used is multiple linear regression. Based on the analysis found that the cash holding positive effect on income smoothing. Profitability positive effect on income smoothing. Reputation auditor negative effect on income smoothing.
Keywords: Income Smoothing, Cash Holding, Profitability, Auditor Reputation